Empowering nurses through action research for developing a new nursing handover program in a pediatric ward in Iran. Issue 2 (June 2017) - Sarvestani, Raheleh S; Moattari, Marzieh; Nasrabadi, Alireza N; Momennasab, Marzieh; Yektatalab, Shahrzad; Jafari, Abdosaleh
This study aimed at developing a new nursing handover program in pediatric wards in Iran through action research. Nursing handover is the handover of patient information among nurses between shifts. The participants, including 12 nurses, 2 assistants, a head nurse, and academic researchers as facilitators, worked through two cycles of reflection and action for change over a period of 20 months from 2012 to 2014. The data were collected and analyzed using the concurrent mixed method. Reflection on actions in two cycles resulted in designing and implementing action plans for change, learning in both participants and facilitators, and improvement in nurses' satisfaction with the new nursing handover program. Furthermore, the quantitative data showed a significant decrease in time and cost of nursing handover. This study resulted in the participants' deep understanding about the principles of nursing handover in real world, applicable knowledge through action for change, and reflection on it. Finally, the nurses could establish the foundation of sustainable nursing handover successfully.